2022
DOI: 10.1093/braincomms/fcac057
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity underlying cognitive and psychiatric symptoms in post-COVID-19 syndrome: is anosognosia a key determinant?

Abstract: Lack of awareness of cognitive impairment (i.e., anosognosia) could be a key factor for distinguishing between neuropsychological post-COVID-19 condition phenotypes. In this context, the twofold aim of the present study was to i) establish the prevalence of anosognosia for memory impairment, according to the severity of the infection in the acute phase, and ii) determine whether anosognosic patients with post-COVID syndrome have a different cognitive and psychiatric profile from nosognosic patients, with assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 102 publications
4
45
2
1
Order By: Relevance
“…Several studies have also shown an impairment of executive functions [ 20 , 25 , 28 , 29 , 30 , 31 , 32 , 33 ] attention [ 20 , 26 , 28 , 30 , 32 , 33 ] and memory [ 24 , 27 , 30 , 32 , 33 ] following COVID-19. In our study, we found that for the 40–59 age group, generative naming time was correlated with PPTT scores: the longer the generative naming time, the better the PPTT scores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have also shown an impairment of executive functions [ 20 , 25 , 28 , 29 , 30 , 31 , 32 , 33 ] attention [ 20 , 26 , 28 , 30 , 32 , 33 ] and memory [ 24 , 27 , 30 , 32 , 33 ] following COVID-19. In our study, we found that for the 40–59 age group, generative naming time was correlated with PPTT scores: the longer the generative naming time, the better the PPTT scores.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using pre- and post-infection imaging data identified a reduction in grey matter thickness, especially in the left hemisphere, and tissue-contrast in the orbitofrontal cortex and parahippocampal gyrus, which are highly connected to the olfactory system [ 26 ]. The damage to certain brain regions as a result of SARS-CoV-2 infection seems to lead to cognitive dysfunction [ 20 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Indeed, the percentage of post COVID-19 patients with global cognitive impairment varies from 15 to 80% [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that post-ICU effects are not the sole cause of long-term neuropsychological deficits ( Sakusic et al., 2018 ), given the high cumulative percentages of memory, executive, perceptual, and logical reasoning deficits in the moderate subgroup. Moreover, this highlights central nervous system involvement, either directly via SARS-CoV-2 neuroinvasive mechanisms, or indirectly via an immunological and/or inflammatory response to SARS-CoV-2 ( Bougakov, Podell, & Goldberg, 2021 ), which is supported by PET-FDG ( Guedj et al., 2021 ), functional connectivity ( Voruz et al., 2022b ), and structural ( Douaud et al., 2022 ) neuroimaging. Another hypothesis, which could explain the greater number of cumulative deficits in moderate patients, concerns the level of hypoxemia, for according to the literature, this is a predictor of cognitive deficits ( Herridge et al., 2016 ; Mikkelsen et al., 2012 ).…”
Section: Discussionmentioning
confidence: 93%
“…Показано, что в среднем через 8 мес после COVID-19 16% пациентов с легкой формой заболевания, 33% со среднетяжелой формой и 35% с тяжелой формой игнорируют нарушения памяти и другие КН, которые ассоциируются с изменениями на МРТ [52].…”
Section: клиническая картина методы обследования и лечение при основн...unclassified